The effectiveness of cinnamon powder and cinnamon leaf extract to prevent Aeromonas hydrophila infection on striped catfish Pangasianodon hypophthalamus - Erni Susanti; Dinamella Wahjuningrum; Sri Nuryati; Mia Setiawati (Jurnal Akuakultur Indonesia)
Striped catfish Pangasianodon hypophthalamus is one of the intensive cultured commodities. Disease outbreak becomes inevitable to prevent in a fish culture. One of the most frequent disease occurred in striped catfish is the motile aeromonas septicemia (MAS) disease caused by Aeromonas hydrophila. This study aimed to evaluate the effectiveness of 1% dietary cinnamon powder and 0.5% dietary cinnamon leaf extract on the immune response of striped catfish challenged with A. hydrophila. Striped catfish used in this study sizing of 5.80 ± 0.21 g. This study contained two phases, namely in vitro and in vivo tests. In vitro test contained inhibition zone and antibacterial tests, which demonstrates that 1% cinnamon powder and 0.5% cinnamon leaf extract are effective to inhibit A. hydrophila activity. In vivo test contained four treatments, i.e fish fed with 1% cinnamon leaf powder supplemented diet; 0.5% cinnamon leaf extract supplemented diet, positive control diet, and negative control diet. Each treatment was performed in three replications. The result showed that 1% cinnamon leaf powder supplemented diet obtained the best results to enhance the immune response of striped catfish higher survival rate value at 83.33% than the positive control diet (P<0.05).